Physio-Chemical Properties of Piperazinediium bis(4-Nitrophenolate)dihydrate: A Non-linear Optical Crystal - Ambika, V. Revathi; Shalini, D.; Usha, R.; Hema, N.; Murugan, M.; Jayalakshmi, D. (Asian Journal of Chemistry, 2017)
Good quality single crystals of piperazinediium bis(4-nitrophenolate)dihydrate (PBPNPD) have been grown from aqueous solution by slow evaporation solution growth technique. Unit cell parameters of the grown crystal were confirmed by single crystal X-ray diffraction analysis and the synthesized compound is crystallized in triclinic system. Various functional groups and their vibrational frequencies were recognized from the FT-IR spectrum. The grown crystal has wider transparency nature in the visible region and the lower cut-off wavelength is found at 329 nm Thermal stability of the crystal was examined by recording the TGA/DTA curve. The dielectric studies were performed. The mechanical properties of the crystal were estimated by Vickers hardness test. The relative second harmonic efficiency (non-linear optical) of the compound is found to be 2.4 times greater than that of potassium dihydrogen phosphate (KDP). The laser damage threshold (LDT) for the grown crystal were measured as 9.43 GW/cm2 with Nd:YAG laser assembly.